Pain treatment in patients with cirrhosis - Gras-Ozimek, Jordi; Kozinska, Urszula (Journal of Education, Health and Sport, 2022)
Chronic pain is reported by 40% -79% of patients with cirrhosis, which is one of the most neglected symptoms among this population. Chronic pain management in patients with cirrhosis remains a difficult clinical issue since a significant number of analgesics are metabolized in the liver and potential side effects are more frequent and involve significant clinical risk. The aim of this review is to draw attention to the available pain management options in patients with cirrhosis based on an analysis of published articles. The following article is based on the literature found in the pubmed database. There are still no precise pain management guidelines in this group of patients. Treatment should include pharmacological, non-pharmacological methods and treatment of comorbidities and patients require careful observation. More research is needed in this area.